2015
DOI: 10.5860/lrts.59n4.187
|View full text |Cite
|
Sign up to set email alerts
|

What Makes an Effective Cataloging Course? A Study of the Factors that Promote Learning

Abstract: This paper presents the results of a research study, a survey of library and information science master’s degree holders who have taken a beginning cataloging course, to identify the elements of a beginning cataloging course that help students to learn cataloging concepts and skills. The results suggest that cataloging practice (the hands-on creation of bibliographic records or catalog cards), the effectiveness of the instructor, a balance of theory and practice, and placing cataloging in a real-world context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This section will focus on previous works about the evaluation of cataloguing courses in general with the original RDA, what constitutes an efficient cataloguing course, and what are the core competencies that a future cataloguer should have, since no similar surveys relating to the application of the new official RDA Toolkit into the curriculum have been conducted. When it comes to teaching cataloguing, it appears that several surveys have shown that students prefer more exercises and practical examples than theory (Kyprianos et al, 2022;Chen & Joyce, 2019;Engelson, 2019;Snow & Hoffman, 2015;Al Hijji & Fadlallah;Mugridge, 2008). Moreover, instructor effectiveness is one of the key topics identified in cataloguing course surveys.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This section will focus on previous works about the evaluation of cataloguing courses in general with the original RDA, what constitutes an efficient cataloguing course, and what are the core competencies that a future cataloguer should have, since no similar surveys relating to the application of the new official RDA Toolkit into the curriculum have been conducted. When it comes to teaching cataloguing, it appears that several surveys have shown that students prefer more exercises and practical examples than theory (Kyprianos et al, 2022;Chen & Joyce, 2019;Engelson, 2019;Snow & Hoffman, 2015;Al Hijji & Fadlallah;Mugridge, 2008). Moreover, instructor effectiveness is one of the key topics identified in cataloguing course surveys.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in Greece, there is no official translation of the basic tools for cataloguing. Cataloguing is not a new course in library and information studies curricula (Snow & Hoffman, 2015). Some principles or rules for the description and categorisation of library items and collections appeared from the beginning of their development.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for this may be the difficulty of delivering this content in an engaging and interactive manner. CAT/CLASS can be complex and technical topics and may require a significant amount of hands-on practice to master (Snow & Hoffman, 2015). However, with the right instructional design and use of technology, it is possible to create engaging and interactive learning experiences that can help learners develop the skills they need to become proficient in CAT/CLASS.…”
Section: Why Is Cataloguing/classification Missing?mentioning
confidence: 99%
“…A large number of current graduate level cataloging courses frame the topic in terms of theory and practice (Joudrey and McGinnis, 2014), that is, learning about cataloging vs. learning to do cataloging (Moulaison, 2012), while the actual decision-making witnessed does not fit neatly into those categories. Given the importance of hands-on cataloging practice and the need to support a more ideal balance of theory and practice in cataloging education (Snow & Hoffman 2015), educators need ways of offering the former without compromising the latter. Drawing on pedagogical techniques from design, including methods for repertoire development, may help address this issue.…”
Section: Beyond Judgment: Repertoire Developmentmentioning
confidence: 99%